The Relationship between Inflation and Economic Growth in Ethiopia - Wollie, Getachew (Budapest International Research and Critics University, 2018)
Since both inflation and economic growth are not a new concept rather their relationships are waited still now as a debatable issue among macro-economists, policy makers, policy analysts, politicians and even the population itself by giving their own analysis by conduct a research and assumption based on the trend as before. Basically, the aims of this seminar paper are to review the relationship between inflation and economic growth as well as to review the causes, sources, determinants and impacts of Ethiopian inflation. Most of the studies indicated above shown that, higher and volatile inflation is bad for the economy. On the other hand, lower and stable inflation is considered as a promoter of the economy. Then the question should focus on what level of inflation is harmful to economic growth? Many economists have made researches on estimating the threshold level of inflation using panel data for a number of countries and time-series data for single country cases and these researchers fix the threshold level of inflation for both developing and developed country. But in this seminar paper, quantifying or fix the exact number of threshold level of Ethiopian inflation and decide below this level inflation has a positive effect on growth and beyond this level it has negative impact on growth is very difficult by simply review previous literature without conducting actual research and make a deep analysis. Even if it is the case, based on the literature it is surely possible to conclude the inflation rate has a serious negative effect on the growth of one country’s economy especially in Ethiopia, if inflation has a double digit of an annual growth.